1997
DOI: 10.1099/0022-1317-78-7-1771
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic accumulation of two plant virus coat proteins on a single self-processing polypeptide.

Abstract: An expression cassette based on the highly specific tobacco etch potyvirus (TEV) nuclear inclusion (NIa) proteinase has been developed to produce multiple proteins through the translation of a single selfprocessing polypeptide. Gene constructs encoding TEV NIa, the tobacco mosaic tobamovirus (TMV) coat protein (CP) and the soybean mosaic potyvirus (SMV) CP were used to develop transgenic tobacco plants. Proper processing of the multifunctional polypeptide was demonstrated, leading to accumulation of separate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Dasgupta et al (1998) used the TVMV NIa proteinase to express two reporter genes (CAT and acetate kinase [AK]) in transgenic tobacco plants. As expected from the reports by von Bodman et al (1995) and Marcos and Beachy (1997), processed and enzymatically active CAT and AK could be observed in the resulting plant lines. Partial processing of a polyprotein bearing cytoplasmicallỳ targeted' CAT and AK was minimal in this report, suggestive of possible differences in processing efficiencies of different NIacontaining polyproteins.…”
Section: Strategies For Polycistronic or Polygenic Transgene Expressisupporting
confidence: 69%
See 2 more Smart Citations
“…Dasgupta et al (1998) used the TVMV NIa proteinase to express two reporter genes (CAT and acetate kinase [AK]) in transgenic tobacco plants. As expected from the reports by von Bodman et al (1995) and Marcos and Beachy (1997), processed and enzymatically active CAT and AK could be observed in the resulting plant lines. Partial processing of a polyprotein bearing cytoplasmicallỳ targeted' CAT and AK was minimal in this report, suggestive of possible differences in processing efficiencies of different NIacontaining polyproteins.…”
Section: Strategies For Polycistronic or Polygenic Transgene Expressisupporting
confidence: 69%
“…It is possible, owing to differences in rates of cis-and trans-processing by embedded proteinases, that picornaviral-like proteinases may act inefficiently on polyproteins that possess large numbers of foreign (e.g., nonviral) polypeptides. It is also possible, as suggested by the contrasting processing efficiencies noted by Marcos and Beachy (1997) and Dasgupta et al (1998), that different proteins may fold or otherwise interact with the processing site or proteinase in a way that leads to less than quantitative processing of the expected polyprotein.…”
Section: Caveats and Prospects For The Use Of Multigene Expression Stmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown that the protein cloned at the C-terminus was produced in a lower amount than the N-terminal protein. Marcos and Beachy (1997), mentioned possible premature termination of translation as a mechanism for imbalance. The reason may be the nuclear localization signals (NLSs) present in the NIa, targeting the polyprotein to the nucleus.…”
Section: Proteolytic Processingmentioning
confidence: 97%
“…Alternatively, incorporating an exogenous protease within the polyprotein system is used to overcome this problem. Some notable examples include polyprotein vectors that employ NIa protease recognition sequence together with the Nla proteinase from the tobacco etch virus (Marcos and Beachy, 1994, 1997) and a similar vector that employs a NIa proteinase from the tobacco vein mottling virus (Dasgupta et al ., 1998). While proper polyprotein processing was achieved using these vectors, the protein expression levels were generally low.…”
Section: Introductionmentioning
confidence: 99%